Grit Description in High/Vocational School Student of Bandung City - Djamhoer, Temi Damayanti; Sartika, Dewi; Nugrahawati, Eni Nuraeni (KnE Social Sciences, 2023)
According to student development tasks for high/vocational school students, selecting and preparing a career is an essential aspect of their development. Therefore, these students must engage in career planning, and one of the factors that significantly influences career planning and maturity is their individual personality or level of Grit. Several components related to career development include career maturity, personality effectiveness, career decision-making, and goal setting. One specific personality factor that aligns with the positive psychology approach is Grit, which encompasses effort, diligence, consistency of interest, and adaptability to various situations. In this research, fifty high/vocational school students from Bandung City were selected as the sample for the study. The researchers used the Grit Scale developed by Duckworth as a measuring instrument to assess the students’ level of Grit. The research method employed in this study is descriptive quantitative to provide an overview and description of the Grit personality among the students. The findings of the research indicate that the overall level of Grit in high/vocational school students from Bandung City is low. Keywords: grit, career development, high/vocational school student